2018
DOI: 10.1017/s0142716418000589
|View full text |Cite
|
Sign up to set email alerts
|

The development of a measure of root awareness to account for reading performance in the Arabic language: A development and validation study

Abstract: Morphological awareness (MA) is an important predictor of reading outcomes in different languages. The consonantal root is a salient feature of Arabic lexical structure and critical to MA. The goals of this study were to (a) develop a measure of root awareness (RA) as one dimension of MA in Arabic, and (b) validate the RA measure by predicting reading outcomes in an Arabic population. A set of RA items was administered to 194 Arabic-speaking third-grade children. A one-factor model was specified using confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
(130 reference statements)
3
14
0
Order By: Relevance
“…These findings thus reinforce the conclusion that there is a link, possibly causal, between MA and reading acquisition in Arabic. They concur with previous evidence of a contribution of MA to word reading ( Abu-Rabia, 2007 ; Saiegh-Haddad and Geva, 2008 ; Boukadida et al, 2009 ; Abu-Ahmad et al, 2014 ; Tibi et al, 2018 ; Tibi and Kirby, 2019 ), pseudoword reading ( Tibi and Kirby, 2017 , 2019 ; Tibi et al, 2018 ) and reading comprehension ( Abu-Rabia, 2007 ; Asadi et al, 2017c ; Layes et al, 2017 ; Tibi et al, 2018 ; Tibi and Kirby, 2019 ). Taken together those findings underscore the role of morphological structure as an important component of Arabic reading development as proposed by Saiegh-Haddad (2018) in her model of Arabic reading acquisition.…”
Section: Discussionsupporting
confidence: 92%
“…These findings thus reinforce the conclusion that there is a link, possibly causal, between MA and reading acquisition in Arabic. They concur with previous evidence of a contribution of MA to word reading ( Abu-Rabia, 2007 ; Saiegh-Haddad and Geva, 2008 ; Boukadida et al, 2009 ; Abu-Ahmad et al, 2014 ; Tibi et al, 2018 ; Tibi and Kirby, 2019 ), pseudoword reading ( Tibi and Kirby, 2017 , 2019 ; Tibi et al, 2018 ) and reading comprehension ( Abu-Rabia, 2007 ; Asadi et al, 2017c ; Layes et al, 2017 ; Tibi et al, 2018 ; Tibi and Kirby, 2019 ). Taken together those findings underscore the role of morphological structure as an important component of Arabic reading development as proposed by Saiegh-Haddad (2018) in her model of Arabic reading acquisition.…”
Section: Discussionsupporting
confidence: 92%
“…The impact of these patterns of reorganization in the maturing brain on language learning was construed by Karmiloff-Smith (1992) as reflecting a process whereby knowledge becomes more integrated, denser, and more readily accessible in adolescence (Tibi, Tock, & Kirby, 2019). Along similar lines, Ramscar and Glitcho (2007) show that language acquisition changes its character from unsupervised learning in early childhood to the more agentive, self-monitored, supervised learning typical of older childhood and adolescence.…”
Section: Later Language Developmentmentioning
confidence: 99%
“…e contributions were still signi cant even aer accounting for grade, gender, and phonological awareness. Another study by Tibi and Kirby (2019) found that morphological awareness, as measured by various morphological awareness tasks, was able to account for unique variations in grade three students' text reading uency and maze reading comprehension measures. Similarly, a longitudinal investigation by Vaknin-Nusbaum and Saiegh-Haddad (2020) found that aer controlling for word reading, morphological awareness at the start of the second grade in Arabic-speaking students predicted success in reading comprehension at the end of the school year.…”
Section: Students With Reading Difficultiesmentioning
confidence: 99%
“…Six studies out of eight (Table 1: 2, 8, 10-13), reported positive correlations between measures of phonological awareness and reading comprehension in typical readers, with the exception of Tibi and Kirby (2019) (Table 1: 9) who explored 3rd grade children, and Asadi (2020) (Table 1: 15) who examined children in 7th and 9th grade. One possible explanation for the lack of observed contribution of phonological awareness reported by Tibi and Kirby (2019) may be due to differences in the hierarchy of predicting variables in the regression analysis (Lankau and Scandura, 2002). e study found that morphological awareness, rather than phonological awareness, was the most important predictive variable for reading comprehension.…”
Section: Typical Readers: Phonological Awarenessmentioning
confidence: 99%